Impact of supplemental irrigation through sprinkler raingun at alternate phenological stages of wheat crop - Abbas, Syed Haider; Islam, Zafar; Shakoor, Abdul; Qamar, Maqsood; Tanveer, Sikander Khan; Hussain, Imtiaz; Majeed, Abid (Journal of Pure and Applied Agriculture, 2024)
In Pakistan, wheat yield in the rainfed area is being affected due to erratic, unexpected pattern of rainfall. Heat stress is also a limiting factor that decreases the grain weight as well as yield badly. Water is a precious finite natural resource in rainfed areas, and its proper utilization is critical for optimizing crop water yield. During wheat growing season 2010-11, research was planned to evaluate various watering treatments at National Agricultural Research Centre (NARC) on wheat crop variety (Chakwal-50). Treatments are applied at three phenological Feeks growth stages viz. Feeks Scale = 2.00 (Tillering), Feeks Scale = 10.50 (Anthesis) and Feeks Scale = 10.5.1 (Grain Filling). The experiment was designed using a randomized complete block design and replicated thrice. The research site perceived 257.7 mm rainfall water during growing season of wheat crop. The 25 mm level of irrigation water produced maximum biological yield (10392 kg/ha), economic yield (3534.3 kg/ha), 1000 grain weight (40.9 g), plant height (90.8 cm) and length of spike (9.3 cm). There were 64% and 55% increments in biological and grain yield kg/ha when level of irrigation water was applied at the rate of 25 mm at Feeks Scale = 2.00, and Feeks Scale = 10.5.1 of wheat as compared to barani at Feeks Scale viz. Feeks = 2.00, Feeks = 10.50 and Feeks = 10.5.1.